Kontribusi Usia dan Konsumsi Makanan Berisiko terhadap Penyakit Jantung di Provinsi Jambi - M. Dody Izhar; Muhammad Syukri (Sarana Ilmu Indonesia (salnesia), 2022)
The prevalence of heart disease in Jambi Province has increased. This study aimed to determine the factors associated with heart disease in Jambi Province. This cross-sectional study used secondary data from the 2018 Basic Health Research (Riskesdas). Data regarding age, gender, type of occupation, domicile, smoking status, physical activity, consumption patterns, and Body Mass Index (BMI) from 15483 were analyzed. The relationship between independent variables and heart disease was analyzed bivariately using the Chi Square Test (X2) followed by multivariate analysis using the Multiple Logistics Regression Test. The results showed that the proportion of heart disease in Jambi Province was 0.96%. Factors related to the incidence of heart disease were age (AOR=4.075; 95%CI=2.735-6.073), consumption of sweet foods (AOR=0.367; 95%CI=0.162-0.831), and consumption of processed foods with preservatives (AOR=2.211). ; 95%CI = 1,290-3.789). The dominant factor associated with heart disease in Jambi Province was age (AOR=4,075; 95%CI=2,735-6.073). It is recommended for the community to be able to maintain a healthy consumption pattern to reduce the risk of heart disease.